Design, simulation and implementation of an Arduino microcontroller based automatic water level controller with I2C LCD display - Akinwole OO (International Journal of Advances in Applied Sciences, 2020)
The paper explains utilization of Arduino Microcontroller to automatically control level of water in a tank. From a well spelt out algorithms, flowchart was drawn, from which Codes were written and compiled on Arduino IDE. IF statements were copiously used. Proteus was used to simulate the design while the project was implemented on breadboard. Liquid Crystal Display function displays the level of water on the 16 × 2 LCD thus: Very Low, Low, High and Very High. An option of I2C LCD codes was written thus providing advantage of using only two analog input A4 and A5 pins instead of 4 to 8 pins in other configurations thereby allowing other pins dedicated for other tasks. The design recommends improvements in the area of sump control so that its low water level could disable pump thus preventing it from running dry. Protection devices like circuit breaker overload and phase failure relays are recommended in order to prolong the life of the Water pump. It is believed that the design will go in long way in educating power electronic engineers in the arts of design using Arduino; also, a mass production of the device will accentuate Small and Medium Enterprises SMEs in developing countries with its concomitant economic advantages.